PLAGUE AS A BIOLOGICAL WEAPON OF MASS DESTRUCTION - Dewi Kartikawati Ningsih (Journal of Nursing Science Update (JNSU), 2013)
Indonesia is an archipelago country lies on the pacific ring of fire, which has a greater risk for disaster due to its geographic location. Indonesia had experienced both natural disaster and man made disaster. However, now days man made disaster often occurred that lead towards destruction of human mankind. Modern weapon of mass destruction are either nuclear, biological or chemical can bring a huge damage to societies and civilization.Â  The method used in this literature review was collected and analyzed the article of biological weapon of mass destruction. Articles collected through electronic databases such as CINAHL; ScienceDirect; Center for Disease Control (CDC); American Medical Association (AMA); National Institute of Allergy and Infectious Diseases (NIH) and textbook of emergency preparedness response. The criteria of articles have full text and published in the period of time between 2004-2014. In this article mainly focused on explaining plague as a biological weapon of mass destruction that including description of the agents, historical background occurring plague as a biological organism, historical use plague as a weapon of mass destruction (WMD), transmission/dispersion/incubation, diagnosis and treatment, detection, responder safety consideration, environmental impact, medical surge consideration and future implications. The huge number of casualties due to sudden event can cause increasing demand for health care resources including facilities, health care providers, hospital resources, infrastructures and other resources. Preparing for medical surge are always in the first priority and can be consisting medical services facilities, medical care providers, hospital resources as well as infrastructures. During tremendous outbreak health care center will probably run out of space, furthermore it is essential to establish the alternate care facilities such as school, mosque, churches, community center, mall, government building, stadium, medical professional offices and so forth to deal with large casualties. In addition, totally eliminating plague is less possible, and so improving prophylactic and therapeutic antibiotic regimen as well as rapid diagnostic and technical laboratory microbiology standards are essential to response plague outbreak. Key word: plague, biological weapon of mass destruction, bioterrorism-related epidemics